Дослiдження Шестовицьких курганiв - Скороход, В.М.; Блажчек, Д. (Археологія, 2020)
Розглянуто нові археологічні дослідження у ІІІ курганній
групі Шестовицького некрополя. Дослідження проведені
у північній частині ІІІ курганної групи, де вибрано два
насипи, що були досліджені однією ділянкою. В одному
з курганів виявлено інгумацію чоловіка з ножем та залишками залізного кістеню, що належить до Х ст. Один
з курганів похованнь Х ст. не містив. У верхній частині
насипу виявлено впускне поховання ХІІ ст. Шестовицкий археологический комплекс состоит из городища, посада, подола и обширного курганного некрополя, в котором Д. Блифельд выделил шесть курганных групп. Курганы Шестовицы исследовались еще с 20-х
годов ХХ в. До сегодняшних дней их было раскопано более 160.
В 2017 г. сотрудниками Института археологии НАН Украины снят новый детальный план некрополя, где были
выделены исследованные и оставшиеся курганы. В целом, в рассматриваемой третьей курганной группе были
насчитаны остатки 20 насыпей. Третья курганная группа Шестовицкого могильника расположена в ур. Диброва
на расстоянии 750 м к западу от городища Коровель, на невысоком возвышении, что в древности омывалось небольшим ручьем старицы р. Десна.
В сезоне 2018 г. украинско-польская археологическая экспедиция исследовала 2 курганных насыпи в северной части третьей группы. Курганы исследовались одной площадью 220 кв. м.
В первом кургане, расположенном в северной части раскопа, исследованы остатки впускного погребения
ХІІ в., которое находилось в верхней части по центру насыпи. Скелет принадлежал подростку и сохранился лишь
частично. Никакого сопутствующего инвентаря и следов могильной ямы зафиксировать не удалось. Погребение
Х в. не выявлено. Вокруг кургана прослеживался курганный ровик. Диаметр кургана — 7,0 × 9,0 м. В западной
части насыпи и частично в верхних слоях заполнения ровика была найдена керамика ХІІ в.
Курган 2 находился южнее предыдущего. До начала исследований его высота была 0,39 м. Курган имел овальную форму и был вытянут с запада на восток 8,2 × 7,2 м. В кургане исследовано погребение мужчины в могильной
яме, ориентированное головой на запад. Скелет лежал в анатомическом порядке с согнутыми в коленях ногами.
Возле правого бедра у погребенного находился железный нож, а под правым коленом — железный восьмигранный
наконечник кистеня. Диаметр кургана был 9,5 × 10 м.
Таким образом, в сезоне 2018 г. было раскопано 2 курганных насыпи в третьей группе Шестовицкого археологического комплекса. Тут выявлено погребение мужчины Х в. и впускное погребение ХІІ в. в одном из курганов
Х в., где погребение отсутствовало, либо не сохранилось. Shestovitsa archaeological complex consists of the hill-fort, the uppertown, the lower city and of the large mound necropolis,
which D. Blifeld divided into six mound groups. Burial mounds have been investigated since 1920’s. More than 160 of them
have already been excavated till nowadays.
In 2017, scientific workers of the Institute of Archaeology of the National Academy of Sciences of Ukraine took a new
detailed plan of the necropolis, where the investigated and remaining mounds were identified. In total, the remains of 20
embankments were counted in the third mound group. The third mound group of the Shestovitsa necropolis is situated in
the Dibrova boundary 750 m to the west from the hill-fort Korovel, at a low elevation, which in ancient times was washed
by a small stream of the old channel of the Desna River.
Two mound embankments in the northern part of the third mound group were excavated by Ukrainian-Polish
archaeological expedition in 2018. Burial mounds were investigated together, their total area of the excavation covered
220 m2
.
The remains of 12th century inlet burial, which was located in the upper part in the center of the embankment, were
investigated in the first mound situated in the northern part of the excavation. The skeleton belonged to a teenager and
preserved partially. No related equipment or traces of the grave pit were fixed. The burial of 10th century was not found.
There was a mound ditch around the embankment. The diameter of the mound was 7.0 × 9.0 m. Fragments of 12th century
ceramics were found in the western part of the embankment and partially in the upper layers of the ditch filling.
The mound no. 2 was situated to the south of the previous one. Before the beginning of the investigations it was 0.39 m
high. The mound had an oval shape and was extended from west to east by 7.2 × 8.2 m. Man’s burial in a grave pit with
the head oriented to the west, was found in it. The skeleton laid in anatomical order with legs bent at the knees. There was
an iron knife near the right thigh bone of the buried, and an iron octagonal tip of the knobstick under his right knee. The
diameter of the mound was 9.5 × 10 m.
Thus, in the 2018 season, two burial moundsin the third group of the Shestovitsa archaeological complexwere excavated.
The burial of the man of 10th century and the inlet burial of 12th century in one of 10th century mounds, where the burial was
absent or not preserved, were found here.